Conformational selection and adaptation to ligand binding in T4 lysozyme cavity mutants - López, Carlos J.; Yang, Zhongyu; Altenbach, Christian; Hubbell, Wayne L. (Proceedings of the National Academy of Sciences - PNAS, 2013)
The studies presented here explore the relationship between protein packing and molecular flexibility using ligand-binding cavity mutants of T4 lysozyme. Although previously reported crystal structures of the mutants investigated show single conformations that are similar to the WT protein, site-directed spin labeling in solution reveals additional conformational substates in equilibrium exchange with a WT-like population. Remarkably, binding of ligands, including the general anesthetic halothane shifts the population to the WT-like state, consistent with a conformational selection model of ligand binding, but structural adaptation to the ligand is also apparent in one mutant. Distance mapping with double electron-electron resonance spectroscopy and the absence of ligand binding suggest that the new substates induced by the cavity-creating mutations represent alternate packing modes in which the protein fills or partially fills the cavity with side chains, including the spin label in one case; external ligands compete with the side chains for the cavity space, stabilizing the WT conformation. The results have implications for mechanisms of anesthesia, the response of proteins to hydrostatic pressure, and protein engineering.